Synthesis and Characterization of Binuclear Complexes of Oxovanadium(IV), Oxozirconium(IV), Dioxouranium(VI) and Thorium(IV) with N,N'-bis[(1E,2E)-2-(Hydroxyimino)-1-phenylethylidine]biphenyl-4,4'-diamine - Z. Bootwala, Sakina (Asian Journal of Chemistry, 2011)
In the present work, the synthesis of oxovanadium(IV), oxozirconium(IV), dioxouranium(VI) and thorium(IV) coordination compounds of tetradentate nitrogen donor ligand N,N'-bis[(1E,2E)- 2-(hydroxyimino)-1-phenyl-ethylidine]biphenyl-4,4'-diamine is described. Their structures were determined on the basis of elemental analysis, molar conductance, magnetic susceptibility, electronic and thermal analysis, 1H NMR and IR spectra. Based on analytical and molar conductance data it is revealing that the ligand (L) is coordinated in (N4) fashion. The complex may be formulated as [VOL]2, [ZrL(H2O)]2, [UOL(H2O)2]2 and [ThL(NO3)2(H2O)2]2. The result indicates that the VO(IV) complex is square pyramidal; ZrO(IV) is hexacoordinate where as UO2 (VI) is 8-coordinated and Th(IV) is 10-coordinated complex.